Contribution of the National Institute for Nuclear, Chemical and Biological Protection to the Development of Methods and Procedures Related to Safety Engineering - Bradka, Stanislav; Mikes, Tibor (Communications - Scientific letters of the University of Zilina, 2008)
The paper describes the National Institute for Nuclear, Chemical and Biological Protection involvements with regards to the development of methods and procedures related to Safety Engineering. It provides general information about the Institute’s activities, history, presence and objectives for the near future to illustrate its role, tasks and responsibilities. The Institute’s added values that consist in its share to the reduction of safety risks and incident consequences are presented and discussed in details.